Impact of a 10-week multimodal stress management and lifestyle modification program on stress response and immune function in Crohn’s disease: a mixed-methods approach using the Trier Social Stress Test - Özlem Öznur; Sandra Utz; Christoph Schlee; Jost Langhorst (Brain, Behavior, & Immunity - Health)
One of the major factors for deterioration and relapse in inflammatory bowel diseases is chronic (psychological) stress. Aim of the present study was to compare the reaction of N = 33 patients with Crohn’s disease that either participated in a multimodal stress management and lifestyle modification program (n = 19) or not (n = 14) to the induction of acute stress after the day-clinic by using the validated instrument of the Trier Social Stress Test (TSST). A mixed-methods approach using self-reported stress perception (questionnaire, qualitative interviews), diary records, and blood samples was applied. Immune and endocrine measures of stress were collected before and repeatedly after stress exposure. Analysis of the blood samples indicated changes in leucocyte and platelet levels only in the intervention group. Differences in the reaction to acute stress might be explained by a significant reduction in perceived (chronic) stress levels in the intervention group compared to baseline (p = .004), whereas there was no change in the control group (p = .472). Diary records (during the day-clinic) showed a notable increase in the number of relaxation techniques (p < .001) and meditative movements (p > .001) performed in the intervention group compared to the control group. In the qualitative interviews (of the intervention group), patients reported a reduction in stress in their daily lives and in acute stressful situations as a result of using the newly learned specific stress management techniques. The observed improvements in stress management (questionnaire, qualitative interviews), indicated by the reduction in perceived stress, and immune function, suggested by the blood sample results, highlight the potential of integrating multimodal stress management and lifestyle changes into the treatment approach for Crohn’s disease patients. Further research is warranted to explore the long-term effects and the multiple mechanisms underlying these observed changes.